Urodynamic findings in women with refractory overactive bladder symptoms. (28th September 2015) - Al‐Zahrani, Ali A; Gajewski, Jerzy
Abstract : Objectives: To assess: (i) the correlation between overactive bladder symptoms and urodynamic findings in female patients; and (ii) the association of urinary symptoms with the presence of detrusor overactivity and/or bladder outlet obstruction. Methods: The present retrospective study included female patients with overactive bladder symptoms who underwent urodynamic evaluation by a single physician. Patients with previous anti‐incontinence surgery or neurogenic bladder were excluded. Spearman's correlation coefficients were calculated to correlate overactive bladder symptoms with the urodynamic findings. Univariate and multivariate logistic regression analyses were used to determine the independent factors for detrusor overactivity and bladder outlet obstruction. Results: Overall, 1737 reports were analyzed. All patients had urgency with or without urgency urinary incontinence. Urgency, urgency urinary incontinence and nocturia correlated with detrusor overactivity. The severity of frequency, nocturia and slow stream correlated with bladder outlet obstruction. In contrast, stress urinary incontinence showed an inverse, but weak, correlation with bladder outlet obstruction. Stress urinary incontinence correlated moderately with urine leak. Storage symptoms showed an inverse, but weak, correlation with maximum cystometric capacity. Multivariate analysis data showed that age, urgency, urgency urinary incontinence and nocturia were independent predictors of detrusor overactivity, whereas the severity of frequency was a predictor of bladder outlet obstruction. Conclusion: As overactive bladder symptoms increase in severity, female patients tend to have a smaller bladder capacity and a higher incidence of detrusor overactivity. A significant number of these patients have bladder outlet obstruction.